Enhanced electrochemical performance of lanthanum ferrite decorated reduced graphene oxide nanocomposite electrodes prepared by in situ microwave irradiation for energy storage applications. (27th October 2020) - Sivakumar, Natarajan; Nagaraju, Perumal; Alsalme, Ali; Alghamdi, Abdulaziz; Jayavel, Ramasamy
Summary: Lanthanum ferrite decorated reduced graphene oxide (LaFeO3/rGO) nanocomposite is prepared by in‐situ microwave irradiation method. The X‐ray diffraction study reveals the single phase orthorhombic structure of LaFeO3 nanoparticles and LaFeO3 /rGO nanocomposites. The FTIR study reveals various vibrational modes and the characteristic D and G bands of the Raman spectrum confirms the formation of reduced graphene oxide. The SEM and HR‐TEM images demonstrate that spherical LaFeO3 particles are decorated on 2D graphene sheets. From the HR‐TEM study, the average particle size of LaFeO3 is estimated to be 23 nm. The synergistic effect of 3D LaFeO3 nanoparticles and 2D graphene layers offers more active sites to achieve the enhanced electrochemical performance. The specific capacitance of LaFeO3 /rGO composites is measured to be 170 Fg −1 at 10 mV s −1 . The composite electrode has admirable cyclic stability, better Columbic efficiency and improved capacitance retention with great potential for supercapacitor applications. Abstract : Novelty of the present investigation is to synthesis LaFeO3 /rGO nanocomposite by low cost in‐situ microwave irradiation method. Uniform decoration of LaFeO3 nanoparticles on the 2D graphene sheets provides more stability of the electrode. The prepared composite electrode material demonstrates higher specific capacitance, Strong cyclic stability and improved capacitive retention.